2009
DOI: 10.4049/jimmunol.0801143
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Essential for Mitochondrial Clearance in Mature T Lymphocytes

Abstract: Macroautophagy plays an important role in the regulation of cell survival, metabolism, and the lysosomal degradation of cytoplasmic material. In the immune system, autophagy contributes to the clearance of intracellular pathogens, MHCII cross-presentation of endogenous Ags, as well as cell survival. We and others have demonstrated that autophagy occurs in T lymphocytes and contributes to the regulation of their cellular function, including survival and proliferation. Here we show that the essential autophagy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
442
10
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 382 publications
(482 citation statements)
references
References 71 publications
18
442
10
5
Order By: Relevance
“…15 Both ATG7 and ATG3 are required for autophagy in T cells. [16][17][18] Previous studies from other groups and our lab indicated that autophagy-deficient conventional T and invariant NKT lymphocytes fail to proliferate efficiently, 12,[18][19][20][21] but the mechanism of the proliferation defect is not clear.…”
Section: Introductionmentioning
confidence: 89%
“…15 Both ATG7 and ATG3 are required for autophagy in T cells. [16][17][18] Previous studies from other groups and our lab indicated that autophagy-deficient conventional T and invariant NKT lymphocytes fail to proliferate efficiently, 12,[18][19][20][21] but the mechanism of the proliferation defect is not clear.…”
Section: Introductionmentioning
confidence: 89%
“…Cellular differentiation often requires extensive morphological changes and intracellular remodeling. Maturation of erythrocytes and T-lymphocytes, for example, requires a reduction in mitochondrial content, which is made possible by autophagy [77,78]. Lack of key autophagy components (e.g., ULK1 or Atg7) results in mitochondrial accumulation and, in the case of Atg7, severely alters blood cell counts [75,77,78].…”
Section: Autophagy In Development and Differentiationmentioning
confidence: 99%
“…Plusieurs éléments justifient le rôle de l'autophagie dans l'activation des LT. Tout d'abord, elle permet à la cellule de répondre à la demande d'énergie qui résulte de la stimulation du TCR [24]. En réduisant le nombre de mitochondries non fonctionnelles, elle prévient de plus l'accumulation de ROS qui favorise l'apoptose [11,12]. L'autophagie régule également le stress du réticulum endoplasmique (RE) en intervenant dans la dégradation sélective de ses membranes [22,23].…”
Section: Autophagie Et éDucation Des Lymphocytes Tunclassified
“…L'autophagie sélectionne les cargos à dégrader. On peut donc penser qu'en absence d'autophagie les défauts de prolifération et de survie observés en réponse à une stimulation du TCR, sont en partie dus à l'expansion du réticu-lum endoplasmique (RE) [22,23] et de la masse mitochondriale [11,12]. L'autophagie permet également de soutenir la demande métabolique en générant des acides aminés (AA) [24].…”
Section: Le Rôle De L'autophagie Dans La Survie Et L'activation Des Lunclassified
See 1 more Smart Citation